The Significance of Elevated Lactate Dehydrogenase and Creatine Kinase Activities as Prognostic Biomarkers for the Mortality in Patients with Terminal Cancers - Qasim J. AL-Daami; Hayder AA. Al-Hindy; Rzaq S. Kaurshead; Rawaa G. Abdullah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Both creatine kinase (CK) and/or lactate dehydrogenase (LDH) mutually are elevatedsignificantly in many tumors. This study hypothesizes that LDH was evaluated as a prognostic factor forsurvival time in patients with terminal cancer (PTC). Additionally, CK considered as a valuable in assessingprognosis of advanced cancer patients. This study aimed to estimate the change in the CK/LDH levelsin patients with different types of cancer comparing with the controls, and to investigate their prognosticsignificance for survival time termination in PTC.Methodology: The study was performed at Cancer Central Research Clinic in Baghdad. We quantitated CK/LDH using the colorimetric method in sixty PTC, and twenty age/sex-matched healthy adults.Results: Serum values of CK/LDH were significantly increased in PTC compared to the controls (p<0.001).There was a weak non-significant correlation between CKLDH in PTC and control. There was a nonsignificantcorrelation of CK to LDH levels in different cancer types, except in patients with lymphaticcancer.Conclusion: In agreement with our hypothesis, serum levels of CK/LDH were significantly increased as thepatients approached death.